(3TQM GHf RGchQ Ydi HOjYjI GdMdis - (3eMeO Hf bGSe Hf eMeO Hf YHO GdhGMO GdaGSj, CHh YHO Gddg, GHf RGchQ , J (B1120 (3g` s; (3GdMdjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde HGdbde Yde GdEfSGf eGde jYde CeG HYO agPG UfjY HOjY ai TQM GdMdjI PGJ GdHOjY HQGYI GdeWdY hJNfjSG GdeQcH hGdeWdb s
(3BNQgG (B:s
(3HQGYI GdNJe Ci GdJCfb ajeG jbY Hg NJe GdcdGe ced GdTQM GdeHGQc HMeO Gddg hLejd Yhfg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdCHjGJ hGdcdeGJ HGdCShO GdSejcs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs